A cryptic RNA-binding domain mediates Syncrip recognition and exosomal partitioning of miRNA targets - Fruzsina Hobor; Andre Dallmann; Neil J. Ball; Carla Cicchini; Cecilia Battistelli; Roksana W. Ogrodowicz; Evangelos Christodoulou; Stephen R. Martin; Alfredo Castello; Marco Tripodi; Ian A. Taylor; Andres Ramos (Nature Communications, 2018)
Syncrip is a conserved RNA-binding protein that mediates selective miRNA loading into cell-secreted exosomes, which is important for cell–cell communication. Here the authors provide mechanistic insights into how Syncrip recognises its target miRNAs by combining NMR and crystallography.